Hysteresis and thermodynamic properties of water sorption in ‘Malagueta’ pepper seeds - Hellismar W. da Silva; Renato S. Rodovalho; Isneider L. Silva (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this study was to determine hysteresis, enthalpy, entropy, enthalpy-entropy compensation theory and Gibbs free energy for water adsorption and desorption in ‘Malagueta’ pepper seeds. Hygroscopic equilibrium moisture contents were determined by the static gravimetric method, with water activity in the range from 0.29 to 0.90 and temperatures of 30, 40 and 50 °C. The hysteresis of the ‘Malagueta’ pepper seeds reduces with the increase of temperature. Enthalpy, entropy and Gibbs free energy of adsorption and desorption increase with the reduction of the moisture content of the seeds. The enthalpy-entropy compensation theory is valid for the sorption processes. The sorption of water between seeds and the surrounding air is a non-spontaneous process.